Separation of gas mixtures using hollow fiber membrane - pilot plant data analysis - Saidi, Hamdani (1989)

(untitled)
The permeation rates and selectivities for a specific permeator are dependent on the type of membrane used and the operating conditions, namely feed pressure, stage cut, temperature and feed composition. This paper presents the experimental study that was carried out on a laboratory scale using hollow fiber Prism separator with a calculated area of 383517.76cm2 to determine effects of two of these operating conditions, feed pressure and stage cut upon permeation rates and selectivities. Compressed air was used as the gas mixture. The range of the feed pressure and the stage cut utilized were respectively 50 psi to 110 psi and 0.0259 to 0.1823.